Physico-chemical characterization of the pulp and peel of Brazilian Pitomba (Talisia esculenta (A. St.-Hill.) Radlk) (Research, Society and Development, 2020)
This study aimed to evaluate the physico-chemical composition and bioactive compounds of pulp and the peel of the pitomba arising from the state of Sergipe/Brazil. The income, the physico-chemical characterization, mineral content, vitamin C and carotenoids of pulp and pitomba peel were determined. The peel presented high income (44,60% of the fruit). A significant amount of vitamin C (20,68 ± 2,93 mg/100g of fresh sample) and carotenoids (43,56 ± 2,04 μg/mL of the extract) were observed in the pulp, while the peel had a high mineral content, mainly potassium (223,00 ± 2,00 mg/100g), calcium (78,90 ± 0,40 mg/100g) and magnesium (47,50 ± 0,90 mg/100g). The constituents’ knowledge of the peel and pulp of the pitomba in natura adds value to the fruit, since it allows a better use of it, considering that the peel is discarded and only its pulp is consumed.